If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x+8=3x-57
We move all terms to the left:
5x+8-(3x-57)=0
We get rid of parentheses
5x-3x+57+8=0
We add all the numbers together, and all the variables
2x+65=0
We move all terms containing x to the left, all other terms to the right
2x=-65
x=-65/2
x=-32+1/2
| -3=27x+5 | | 6a+6(1-6A)=144 | | 5×+4x-68=34-8× | | -5=5x+4 | | 2(x+8)=8(x+1) | | 6+2x/5=92 | | 5−4y+y−1=−23 | | 78=6(-6a-30) | | 2n-18=180 | | -12x-5=-137 | | 2+3(x-7)=2-8(x-9) | | -4(x-2)=3(x+1)+4 | | 50+20+0.25x=50+0.35 | | 4s–74=s+19 | | d=28(2)-5(2)^2 | | 3(4+2x)+x=)26 | | 2(-7+6n)-2(n-10)=-21 | | 2s-31=3s+62 | | 10c+9=-29 | | 7(6x+9)=81 | | 2c=c+61 | | 2(5–n)=n-20 | | 2w-8+3(4w+5)=-4(w+2) | | 3(x+1)=8x+1-5x+2 | | -3x+7=-3x-4 | | |-3x-45|=|-12x| | | -3x+7=-3x+2 | | 4+2(6x-5)=-2(4x-6)+5x | | 2x-(5x-7)=-6x+10 | | 7=x+5x+1 | | -3x+7=-3x+5 | | 4+2(6x-5)=-24x-6)+5x |